2008
DOI: 10.22230/cjc.2008v33n3a1981
|View full text |Cite
|
Sign up to set email alerts
|

Laptops in the Living Room: Mobile Technologies and the Divide between Work and Private Time among Interactive Agency Workers

Abstract: This article examines how mobile technology use affects the division between private and work time among workers in interactive advertising agencies. These workers are frequent users of both personal and company-issued mobile technology. This article investigates the strategies workers use to restrict workplace access during their private time. Relying on the social construction of technology as a point of departure, this article investigates the impact of mobile technologies, as well as the organizational con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…increased perceived workload) due to the possibility to be able to work 24/7 has been expressed in several qualitative studies (Barley et al 2011;Cavazotte et al 2014;Currie and Eveline 2011;Noble and Lupton 1998). Work extension in terms of longer work hours has also been reported in qualitative studies attributing longer work hours to ICT use (Allen and Shoard 2005;Cavazotte et al 2014;Currie and Eveline 2011;Ladner 2008;Mazmanian 2010;Middleton 2007;Noble and Lupton 1998;Porter and Kakabadse 2006;Prasopoulou et al 2006;Stoner et al 2009;Towers et al 2006), which has also been found in several quantitative studies (Duxbury et al 1992(Duxbury et al , 1996Towers et al 2006). Further quantitative studies have also reported the extension of work hours as an antecedent of ICT use (Adkins and Premeaux 2014;Schieman and Glavin 2008).…”
Section: Job-related Characteristics and Work Processesmentioning
confidence: 94%
See 4 more Smart Citations
“…increased perceived workload) due to the possibility to be able to work 24/7 has been expressed in several qualitative studies (Barley et al 2011;Cavazotte et al 2014;Currie and Eveline 2011;Noble and Lupton 1998). Work extension in terms of longer work hours has also been reported in qualitative studies attributing longer work hours to ICT use (Allen and Shoard 2005;Cavazotte et al 2014;Currie and Eveline 2011;Ladner 2008;Mazmanian 2010;Middleton 2007;Noble and Lupton 1998;Porter and Kakabadse 2006;Prasopoulou et al 2006;Stoner et al 2009;Towers et al 2006), which has also been found in several quantitative studies (Duxbury et al 1992(Duxbury et al , 1996Towers et al 2006). Further quantitative studies have also reported the extension of work hours as an antecedent of ICT use (Adkins and Premeaux 2014;Schieman and Glavin 2008).…”
Section: Job-related Characteristics and Work Processesmentioning
confidence: 94%
“…In qualitative research, employees have frequently expressed the perceived pressure exerted by their organizational context to be constantly available and to engage in work-related ICT use during non-work time (Barley et al 2011;Cavazotte et al 2014;Currie and Eveline 2011;Crowe and Middleton 2012;Golden 2013;Harmer et al 2008;Ladner 2008;Lowry and Moskos 2008;Maliszewski 2013;Matusik and Mickel 2011;Mazmanian 2010Mazmanian , 2013Mazmanian et al 2006Middleton 2007;Porter and Kakabadse 2006;Quesenberry and Trauth 2005;Schlosser 2002;Stoner et al 2009;Towers et al 2006). Matusik and Mickel (2011) further outlined that perceived pressure to be responsive is more frequently reported with a high number of different expectation sources (e.g.…”
Section: Social-normative Organizational Contextmentioning
confidence: 99%
See 3 more Smart Citations